PROFITABLE PERCOLATIONS: THE IMPACT OF OPERATIONAL EXCELLENCE AND DIGITAL ENGAGEMENT ON COFFEE INDUSTRY DYNAMICS - Nurul Yaqin; Rita Ambarwati (Antis Publisher, 2026)
Objective: The objective of this research is to examine the correlations between consumer and operational focus and their effects on business outcomes and to investigate the influence of these factors on employee engagement and involvement in do-it-yourself (DIY) models within the framework of digital marketing tactics. Method: A quantitative methodology was employed to conduct a survey targeting coffee shop owners and managers in East Java who had a minimum tenure of six months in their respective roles. The researchers utilized accidental sampling to select participants for the study, and data analysis was conducted using PLS-SEM. Results: The resulthavef the study validate the notion that placing emphasis on customer and operational aspects has a substantial role in enhancing corporate performance. Moreover, the improvement of these outcomes has a favorable impact on staff concentration and fosters increased engagement among coffee shop proprietors in the region of East Java. Novelty: One notable aspect of this study is the integration of Total Quality Management (TQM) characteristics and DIY model factors in evaluating business outcomes, which holds particular significance for coffee street shop owners and managers in Indonesia.